"We're not magicians!" On the use of rhetorical resources in Swedish news media narratives portraying the social services and social workers. (March 2019) - Blomberg, Helena
This article focuses on how the Swedish news media depicts the functioning of the social services and the situation of social workers. The empirical material consists of 586 articles published online during the years 2010–2015. A discursive approach makes up the theoretical and methodological framework. The aims of the article are to identify and categorise media narratives about social services and social workers, how they are portrayed, what is conveyed and how the stakeholders' (politicians, managers and social workers) negotiate the question of responsibility for the situation in the social services. The study identifies and categorises seven different types of media narrative. In these narratives, social workers are portrayed in various ways, such as unwilling to stay in the profession, concerned, hardworking, etc. Reports on the crisis in the social services tend to dominate, e.g. how the social services fail to follow-up cases of child abuse, social workers' heavy workload and that legal security cannot be guaranteed. Stakeholders, faced with reported criticism, maintain credibility by taking some responsibility and/or displacing liability by using various rhetorical resources. The media produces a public image of the lack of responsibility for solving the problematic situation. In this respect, the take-action-narratives are central to the debate, which argues for joint action to be taken to find solutions. Although the media is a powerful and scrutinising tool, it also needs to report on the improvements that have been made in order to give a more balanced picture of the social services.